Breeding cassava for adaptation to stress conditions: development of a methodology - Hershey, Clair H. (1984)
A description is given of CIAT's cassava breeding program, designed to exploit the adaptation of cassava to various physical and biological stress factors by selection over a range of moderate to high stress environments. The selection environments are described and a decentralized breeding methodology is outlined.